Analysis of Entrepreneurial Education Through The Kid's Market Day In Islamic Elementary School - Fahyuni, Eni Fariyatul; Rindaningsih, Ida; Latifah, Fitri Nur; Fanani, Yopi Agusta (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
His study aims to analyze entrepreneurship learning through Kids' Market Day activities for elementary school students in Sidoarjo Regency. This study employs a descriptive qualitative research method, focusing on the analysis of entrepreneurship learning through Kids' Market Day activities for students at Muhammadiyah 1 Elementary School in Sidoarjo. The sources of information in this study included the principal, curriculum head, teachers, students, and parents. Data collection techniques used interviews, observations, and documentation. Data reduction is a data analysis technique used in this study. Data presentation involves describing the results of field research. Data presentation is done through several stages, namely: (1) recording all data findings in the form of field notes, based on the results of interviews, observations, and documentation that have been carried out; (2) reduction and review of relevant interview, observation, and documentation data; (3) classification of relevant research data; and (4) analysis of research report results by triangulating research data. The results of the study indicate that the Kids Market Day activities implemented at Muhammadiyah 1 Elementary School in Sidoarjo have a significant impact on the development of students' entrepreneurial character from an early age, including self-confidence, responsibility, the courage to take risks, and the ability to manage finances. The implications of this research's findings for education and school policy include strengthening project-based curricula and fostering student character through Kids Market Day activities, which foster entrepreneurial values.